Kolaviron via anti-inflammatory and redox regulatory mechanisms abates multi-walled carbon nanotubes-induced neurobehavioral deficits in rats (2020)
Exposure to multi-walled carbon nanotubes (MWCNTs) reportedly elicits neurotoxic effects. Kolaviron is a phytochem- ical with several pharmacological effects namely anti-oxidant, anti-inflammatory, and anti-genotoxic activities. The present study evaluated the neuroprotective mechanism of kolaviron in rats intraperitoneally injected with MWCNTs alone at 1 mg/kg body weight or orally co-administered with kolaviron at 50 and 100 mg/kg body weight for 15 consecutive days. Following exposure, neurobehavioral analysis using video-tracking software during trial in a novel environment indicated that co-administration of both doses of kolaviron significantly (p < 0.05) enhanced the locomotor, motor, and exploratory activities namely total distance traveled, maximum speed, total time mobile, mobile episode, path efficiency, body rotation, absolute turn angle, and negative geotaxis when compared with rats exposed to MWCNTs alone. Further, kolaviron markedly abated the decrease in the acetylcholinesterase activity and antioxidant defense system as well as the increase in oxidative stress and inflammatory biomarkers induced by MWCNT exposure in the cerebrum, cerebellum, and mid-brain of rats. The amelioration of MWCNT-induced neuronal degeneration in the brain structures by kolaviron was verified by histological and morphometrical analyses. Taken together, kolaviron abated MWCNT-induced neurotoxicity via anti-inflammatory and redox regulatory mechanisms.